Effects of feed processing on ration utilization - Jensen, A.H.; Koch, B.A.; Deyoe, C.W. (Kansas Agricultural Experiment Station, 2011)
Previous reports from the Kansas Station have shown that method of processing grains and rations may affect acceptance by the animal and efficiency of utilization. The experiment reported here was designed to evaluate the effects of grinding fineness (of milo and wheat) on feeding value for growing swine.
Keywords: Swine; Grain fineness; Wheat; Milo